2021
DOI: 10.2174/0929866527666200813201924
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Homologues, Pathogenesis-Related 1, Polygalacturonase, and Pectin Methyl Esterase from a Japanese Hop

Abstract: Background: Japanese hop is an important cause of weed pollinosis in East Asia. Its pollen is abundant in autumn. This pollen is known to be the cause of many allergic diseases. However, molecular characteristics of its allergens have not been elucidated. Objective: In this study, we produced recombinant proteins of allergen homologues from Japanese hop by the analysis of expressed sequence tags (EST), and evaluated its allergenicity. Methods: cDNA library was constructed using as little as 50 ng of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 19 In our investigation, the observed IgE reactivity to Hum j 6 together with PME could have resulted in IgE reactivity to a 50 kDa component due to poor dissociation in the protein gel. In previous study, Japanese hop PME demonstrated only weak IgE reactivity 5 ; however associated with PMEI the observed IgE binding as well as inhibition with purified natural Hum j 6 could be explained.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… 19 In our investigation, the observed IgE reactivity to Hum j 6 together with PME could have resulted in IgE reactivity to a 50 kDa component due to poor dissociation in the protein gel. In previous study, Japanese hop PME demonstrated only weak IgE reactivity 5 ; however associated with PMEI the observed IgE binding as well as inhibition with purified natural Hum j 6 could be explained.…”
Section: Discussionmentioning
confidence: 80%
“… 3 Several proteins belonging to allergenic families, such as pathogenesis-related 1 (PR-1) protein, pectin methylesterase (PME), polygalacturonase, and profilin, were identified in HJ pollen by expressed sequence tag analysis, but displayed low allergenicity. 4 5 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, screening a cDNA expression library revealed that a PR-1 protein from Japanese hop ( Humulus japonicus ), an important cause of weed pollinosis in East Asia, is recognized by IgE from 3.4% (1/29) of Japanese hop allergic patients with a positive case history and IgE-sensitization to Japanese hop ( 62 ). Hum j PR-1 encodes for a 171 aa peptide (apparent MW of 20 kDa) and shares 40–46% of aa-sequence identity with Art v 2, Cuc m 3, and Cyn d 24 ( Table 1 ).…”
Section: Pr-1 Allergensmentioning
confidence: 99%
“…A 10 kDa component is known to be a major allergen ( 7 ) even though it has not been cloned. Recombinant proteins of profilin, pathogenesis-related 1, polygalacturonase, and pectin methyl esterase, homologous to pollen allergens from Japanese hop, were recognized with 3.4 to 13.8% of IgE antibodies from the patients ( 9 , 10 ).…”
Section: Inhalant Allergens Of Regional Importancementioning
confidence: 99%